PENGEMBANGAN APLIKASI PERTANDINGAN KARATE BERBASIS ONLINE - Fitromel, Decky; Boy Indrayana; Wawan Junresti Daya; Atri Widowati; Ugi Nugraha; Alek Oktadinata; Agus Parman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of digital technology has significantly transformed sports management systems, including competition organization and scoring mechanisms. However, karate tournaments in many regions of Indonesia are still conducted using manual systems, leading to inefficiencies, scoring inaccuracies, and limited transparency. This study aimed to develop an online-based karate competition application called Digimatch using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research employed a Research and Development (R&D) approach involving needs analysis, expert validation, small-scale trials, and user response evaluation. The subjects consisted of 3 IT experts, 3 karate referees, and 30 users (committee members and coaches). Data were collected using validation sheets and user response questionnaires. Data analysis utilized descriptive percentage techniques to determine product feasibility and effectiveness. The results showed that the application achieved a feasibility score of 91.4% from IT experts (very valid), 88.7% from karate referees (very appropriate), and 89.6% from users (very practical). Implementation testing demonstrated improved efficiency in match administration (32% faster), reduced scoring errors, and real-time result transparency. The findings indicate that Digimatch is valid, practical, and effective in supporting karate competition management. It can be concluded that the Digimatch application provides an innovative solution to modernize karate tournaments, enhance transparency, and support sports digitalization in Indonesia.